A dramaturgia performática de César Brie e Mickaël de Oliveira: textos, contextos e processos de criação junto aos grupos Teatro de los Andes, da Bolívia, e Colectivo 84, de Portugal - Eder Rodrigues da Silva (2017)
The present thesis focuses on studies about dramaturgy as an expanded term, as well as its praxis and the work standpoints of the theatrical text on contemporary scene. Questions raised here aim to analyze how the dramaturg's role is reshaped on the current contextcoming from the new relations established on his/her practical work, the aesthetical developments, and the political dimension embedded into the notion of dramaturgy as an experience space. The referential pathways point towards broader fields of this work and acknowledge the dramaturg as an agent who, while a performer, creates new proceduralwriting ways in its relation to the performance. The work of the dramaturgs chosen as an example for this thesis, César Brie e Mickaël de Oliveira, highlights this conceptual bias based on a plural view about the text in relation to the traditional sources of production and, also, about the collective and performative nature of its genesis. By expanding theweaving of the network that encompass these knowledge, this thesis seeks to dialogue with the numerous dramaturgical practices expressed by the contemporary repertoire..